DINAMIKA PENGGUNAAN AMBANG BATAS PRESIDEN DALAM SISTEMPRESIDENSIAL DI INDONESIA - Fakhris Lutfianto Hapsoro; Ismail (Komisi Yudisial RI, 2026)
This study examines the regulatory framework and legal dynamics of the presidential threshold in Indonesian electoral law, focusing on Judgment Number 62/PUU-XXII/2024 of the Constitutional Court, which declared the presidential threshold provision unconstitutional. The Constitutional Court held that applying the presidential threshold exceeded the permissible limits of the open legal policy doctrine, especially regarding democratic morality, rationality, and justice. This research analyses the doctrinal evolution of the presidential threshold as reflected in the judgment and evaluates its implications for the presidential system. The study uses a normative juridical method, employing case, statutory, and conceptual approaches. The findings indicate that, procedurally, the Constitutional Court expanded legal standing beyond citizens with the right to be elected to include those with the right to vote. Substantively, the Constitutional Court determined that the presidential threshold—previously classified as an open legal policy—violates the doctrine's internal limits. It is inconsistent with democratic morality, policy rationality, and the principle of justice, making it unconstitutional. The abolition of the presidential threshold has significant implications for the presidential system, especially in enhancing the inclusiveness of political rights and creating opportunities to strengthen the institutionalisation of political parties. However, it also raises challenges related to governmental consolidation and political stability. Therefore, strengthening the role and institutional capacity of political parties is essential to advancing a more representative, accountable, and sustainable democratic system.